2014
DOI: 10.1371/journal.ppat.1003885
|View full text |Cite|
|
Sign up to set email alerts
|

Malaria-Induced NLRP12/NLRP3-Dependent Caspase-1 Activation Mediates Inflammation and Hypersensitivity to Bacterial Superinfection

Abstract: Cyclic paroxysm and high fever are hallmarks of malaria and are associated with high levels of pyrogenic cytokines, including IL-1β. In this report, we describe a signature for the expression of inflammasome-related genes and caspase-1 activation in malaria. Indeed, when we infected mice, Plasmodium infection was sufficient to promote MyD88-mediated caspase-1 activation, dependent on IFN-γ-priming and the expression of inflammasome components ASC, P2X7R, NLRP3 and/or NLRP12. Pro-IL-1β expression required a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(153 citation statements)
references
References 74 publications
(97 reference statements)
3
145
3
2
Order By: Relevance
“…These results add a component of the innate immune system to the recently demonstrated essential participation of heme-induced TLR4 activation in sickle cell disease (29,30). Moreover, inflammasome activation is likely important in malaria pathogenesis (45,66). Thus, understanding the molecular signaling pathways affected by heme might prove useful to the identification of new options for treating pathological conditions that have increased extracellular heme.…”
Section: Discussionmentioning
confidence: 73%
“…These results add a component of the innate immune system to the recently demonstrated essential participation of heme-induced TLR4 activation in sickle cell disease (29,30). Moreover, inflammasome activation is likely important in malaria pathogenesis (45,66). Thus, understanding the molecular signaling pathways affected by heme might prove useful to the identification of new options for treating pathological conditions that have increased extracellular heme.…”
Section: Discussionmentioning
confidence: 73%
“…Pyroptosis involves caspases-1, -4, and -5 and is inherently proinflammatory, whereas apoptosis involves caspase-2, -3, -6, -7, -8, -9, and -10 and occurs in the absence of inflammation (20). Although extensively studied in bacterial infections (21,22), the roles of pyroptosis in viral infections were just recently recognized (14,23). While the elegant ex vivo study demonstrated that pyroptosis induced by abortive HIV-1 infection is the predominant means of CD4 ϩ T cell depletion in HIV-1 infection (14), the in vivo role of pyroptosis in CD4 ϩ T cell death in HIV-1/simian immunodeficiency virus (SIV) infection, especially in very early infection, remains largely unknown.…”
mentioning
confidence: 99%
“…It was also involved in caspase-1 activation in response to Yersinia pestis and Plasmodium infection (Vladimer et al, 2012;Ataide et al, 2014). The role of NLRP12 in NF-κB-mediated signaling makes it an important regulator of immune response after Salmonella infection and during colorectal cancer (Zaki et al, 2014) AIM 2 inflammasome AIM 2 (absent in melanoma 2) is a cytosolic dsDNA sensing inflammasome activated by bacterial, viral, and mammalian host DNA to trigger caspase-1 activation (Nakahira et al, 2011).…”
Section: Nlrp12mentioning
confidence: 99%